How does asthma coexistence affect the strategic selection of biologic therapies in CRSwNP management? - Ozdemir, Imran; Bayar Muluk, Nuray; Yazır, Mustafa; Cingi, Cemal (Frontiers in Allergy, 2025)
ObjectivesWe reviewed asthma coexistence and the selection of biologic therapies in CRSwNP Management.MethodsThe literature review utilized Google and Google Scholar, in addition to PubMed, EBSCO, and Proquest Central at Kırıkkale University. We searched for “ CRSwNP”, “asthma”, “biologic therapies”, “Anti-IL-4RA”, “Dupilumab”, “Anti-IgE”, “Omalizumab”, “Anti-IL-5”, “mepolizumab” from 2024 to 2000.ResultsPatients with CRSwNP frequently have co-occurring lower airway illnesses, including asthma and AERD asthma, which have a shared pathogenesis. The inflammatory bases of CRSwNP and asthma might be heterogeneous, with a type 2 or, less frequently, a non-type two inflammatory history. Lower airway inflammation and asthma control are worse in patients with asthma who also have CRSwNP. Patients with CRSwNP can now access targeted biologic medicines, a novel therapy option. The US Food and Drug Administration (FDA) has authorized three medications for CRSwNP: dupilumab, omalizumab, and mepolizumab. To treat chronic rhinosinusitis with a biological agent, the 2020 European position paper on rhinosinusitis established clear indications. A patient is considered a biologic therapy candidate if they have either undergone FESS before or did not meet FESS criteria but met three of the five. A diagnosis of concomitant asthma, necessitating an inhaled glucocorticoid controller regularly, is one of the five requirements.ConclusionBiologic treatments have the potential to be used in certain patients where CRSwNP and asthma coexist. The recommended treatments include omalizumab, dupilumab, and mepolizumab.